Delineating species in the speciation continuum: A proposal. (25th March 2019) - Galtier, Nicolas
Abstract: Delineating species is a difficult and seemingly uninteresting issue that is still essential to address. Taxonomic methodology is heterogeneous according to the taxa and scientists involved due to the disparate data quality and quantity and disagreements over the species concept. This has negative impacts on basic and applied research. Genomic data substantially enhance our understanding of the speciation process but do not provide a ubiquitous solution to the species problem. The relevance of comparative approaches in speciation research has nevertheless recently been demonstrated. I suggest moving towards a more unified taxonomic classification through a reference‐based decision procedure.